Analysis Of The Effectiveness Of Destroyed Land Management In National Strategic Projects (Case Study: Semarang - Demak Toll Road) - Maylia Sita Aifadianis (Faculty of Law, Universitas Negeri Semarang, 2025)
This study aims to analyze the effectiveness of regulatory implementation concerning the management of destroyed land within the National Strategic Project (PSN) of the Semarang–Demak Toll Road. The primary issues examined include the gap between legal norms and social realities, technical obstacles in identifying destroyed land, inequities in compensation assessment methods, low community participation, and weak inter-agency coordination. The research employed a juridical-empirical method with a qualitative approach, combining literature review and field data analysis through observation and documentation. The findings indicate that although the legal framework is in place, field implementation faces significant challenges. Many community members have lost land rights due to the disappearance of ownership documents caused by abrasion and tidal flooding. The identification and verification process is hindered by technical limitations and the absence of standardized guidelines. Furthermore, the initial compensation scheme, which was based on the Tax Object Sales Value (NJOP), did not reflect the real economic or socio-cultural value of the lost land, leading to community rejection. Subsequent policy revisions involving the Public Appraisal Service Office (KJPP) improved fairness in compensation assessment, although the process required considerable time and extensive advocacy. Minimal community participation and weak institutional coordination further exacerbated the challenges of regulatory implementation. The study concludes that the effectiveness of the destroyed land management regulations is largely influenced by the policy’s ability to accommodate socio-economic complexities and to ensure active community involvement in every stage of decision-making.